2004
DOI: 10.1097/00054725-200411000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Infliximab on Apoptosis and Reverse Signaling of Monocytes from Healthy Individuals and Patients with Crohn’s Disease

Abstract: Apoptosis of monocytes is not responsible for the therapeutic effects of infliximab. However, some of the therapeutic effects of infliximab may be caused by its ability to down-regulate proinflammatory cytokines production by monocytes exposed to bacterial antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
1
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 30 publications
(36 reference statements)
2
42
1
2
Order By: Relevance
“…For example, one study found no increase in the number of apoptotic cells when PBMCs isolated from patients with CD were cultured overnight in the presence of INF [48]. In fact, the researchers believed that these cells were stabilized against apoptosis.…”
Section: Effect On Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study found no increase in the number of apoptotic cells when PBMCs isolated from patients with CD were cultured overnight in the presence of INF [48]. In fact, the researchers believed that these cells were stabilized against apoptosis.…”
Section: Effect On Apoptosismentioning
confidence: 99%
“…1). Ringheanu et al [48] found that INF induced "reverse signaling" in isolated PBMCs in vitro to downregulate the production of inflammatory cytokines. They showed that monocytes produced less TNFα after they had been exposed to LPS or SEA when cultured with INF.…”
Section: Effect On Cytokine Productionmentioning
confidence: 99%
“…It neutralizes TNF-a, 15 and induces apoptosis of activated T cells and lymphocytes in the lamina propria thereby reducing the levels of IL-1, IL-6, IL-18 and IFN-g both in vivo [16][17][18] and in vitro. [19][20][21] In the present investigation we determined the changes in the levels and gene expression of the adhesion molecules PECAM-1, ICAM-1 and vascular cell adhesion molecule-1 (VCAM)-1 in two different in vitro models of inflammation, phytohaemagglutinin (PHA)-and LPS-stimulated PBLs, and we defined which adhesion molecules are restored by infliximab treatment in activated leukocytes. In addition, the expression profiles of the genes encoding human PECAM-1 and ICAM-1 in a promonocytic cell line U-937 (a model used to study macrophages biological functions) in response to treatment with PHA and LPS have been defined and using these two models the effect of the anti-TNF-a antibody, infliximab, on PECAM-1, ICAM-1 and VCAM-1 gene expression was determined.…”
mentioning
confidence: 99%
“…First, it is a TNF-␣ neutralizer, binding both monomeric and trimeric forms of this cytokine (32). Second, infliximab causes apoptosis of activated T cells and lamina propria lymphocytes (LPLs) (7,11,22,28,33,36,37). Its ability to induce apoptosis of monocytes is controversial as shown by conflicting in vitro data (22,28).…”
mentioning
confidence: 99%
“…Its ability to induce apoptosis of monocytes is controversial as shown by conflicting in vitro data (22,28). Similarly, monocyte counts decline with infliximab infusion in some studies (21,25) but not others (28). Third, infliximab alters cytokine secretion in the serum and lamina propria, decreasing IL-1, IL-6, IL-18, and IFN-␥ production (2,3,4,8,10,21,25,26,28).…”
mentioning
confidence: 99%